(untitled) (Scientific journal of the Fergana State University, 2023)
The influence of flocculant concentration on the degree of waste water clarification, removal of dyestuffs and COD was established. The effectiveness of flocculation of kaolin and bentonite suspensions with different initial concentrations was revealed. It is determined that the cleaning efficiency is achieved at a concentration of kaolin and bentonite of 2.0 mg/l and flocculant of 0.5 mg/l.